An integrative approach for the selection of Pochonia chlamydosporia isolates for biocontrol of potato cyst and root knot nematodes - Maria Clara VIEIRA DOS SANTOS; Joana HORTA; Luísa MOURA; David PIRES; Isabel CONCEIÇÃO; Isabel ABRANTES; Sofia COSTA (Phytopathologia Mediterranea, 2019)
The nematophagous fungus Pochonia chlamydosporia, a natural enemy of plant parasitic nematodes (PPN), has been exploited in the development of sustainable management strategies for PPN control. The intrinsic variation among P. chlamydosporia isolates affects biocontrol potential, so sound characterisation is required. Biological, molecular and metabolic analyses can be determinant in the screening and selection of these potential biological control agents. This study aimed to provide integrative characterisation of P. chlamydosporia isolates that can support isolate selection for biological control purposes. Eight Portuguese isolates, associated with Meloidogyne spp., were used as a case study. Isolates were identified and characterised: i) at the biological level through standard bioassays to evaluate their ability for rhizosphere colonisation, to produce chlamydospores, and to parasitise Globodera pallida and Meloidogyne incognita eggs; ii) at the molecular level, examining genetic variation using ERIC-PCR; and iii) at the metabolic level, assessing their metabolic profiles using Biolog FF MicroPlates, with concurrent reads of fungal utilisation of 95 different carbon sources. Molecular data and metabolic characterisation were reduced using Principal Component Analysis and compared with the biological characteristics. Molecular profiles could only be related to isolate geographical origin, but the original substrate (eggs or roots), parasitism of M. incognita eggs and ability for rhizosphere colonisation were correlated with metabolic profiles, indicative of utilisation of specific carbon sources. Meloidogyne egg parasitism and rhizosphere colonisation were related to each other. This integrative characterisation offers novel perspectives on the biology and biocontrol potential of P. chlamydosporia, and, once tested on a broader set of isolates, could be used to assist rapid isolate selection.